2019
DOI: 10.1111/are.13983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding a fish meal-free soy protein concentrate-based diet on the growth performance and nutrient utilization of red sea bream (Pagrus major )

Abstract: Two groups of red sea bream (average body weight 85 g) were fed to satiation fish meal (FM) or FM‐free soy protein concentrate (SPC)‐based diet (FM‐sat and SPC groups respectively). A third group (FM‐pair) was fed the same amount of FM as of SPC fed to SPC‐sat group for 6 weeks. Growth rate of SPC group was significantly slower than of FM‐sat and FM‐pair groups (p < 0.05). Feed conversion ratios of FM‐sat and FM‐pair groups were similar and were better than that of SPC group (p < 0.05). Visceral fat somatic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…The SGR and FCR of Basal‐ and FMH diets‐fed fish were significantly lower than those of FM diet‐fed fish following similar feed intake of the diets. The result is consistent with that of our previous study where we observed lower growth performance in fish fed with SPC‐based diet than in those fed with FM‐based diet by paired feeding (similar feed intake) (Tola et al, ). Conversely, lower growth performance observed following the feeding of SPC‐based diet was counteracted by increased feed intake, as demonstrated by the comparable growth induced by FMHG diet with a significantly higher feed intake.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The SGR and FCR of Basal‐ and FMH diets‐fed fish were significantly lower than those of FM diet‐fed fish following similar feed intake of the diets. The result is consistent with that of our previous study where we observed lower growth performance in fish fed with SPC‐based diet than in those fed with FM‐based diet by paired feeding (similar feed intake) (Tola et al, ). Conversely, lower growth performance observed following the feeding of SPC‐based diet was counteracted by increased feed intake, as demonstrated by the comparable growth induced by FMHG diet with a significantly higher feed intake.…”
Section: Discussionsupporting
confidence: 93%
“…Whole‐body lipid content at end of the feeding study tended to be lower in fish fed with SPC‐based diet, although the chemical composition was not significantly different except for ash content. Similarly, in our previous study on red sea bream, whole‐body lipid content in fish fed with SPC‐based diet was significantly lower than that in fish fed with FM‐based diet by paired feeding (equivalent DFR) (Tola et al, ). Low lipid digestibility has been previously reported when SBM was included in the diets of rainbow trout (Watanabe, Pongmaneerat, Sato, & Takeuchi, ) and yellowtail ( Seriola quinqueradiata ) (Nguyen, Khaoian, Fukada, Suzuki, & Masumoto, ).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Researchers have attempted to reduce fish meal with plant protein feedstuff (PP) in aquafeed; nevertheless, the use of these PP in fish diets is hindered due to the presence of a diversity of antinutrient factors and indigestible carbohydrates (Gatlin et al, 2007; Hardy, 2010), reduction of apparent digestibility of coefficients (ADCs) especially for proteins, low palatability (Jannathulla et al, 2018; Mirzakhani et al, 2020) and deficiency in essential amino acids (Sabbagh et al, 2019; Tola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Low feed intake was commonly recognized as a characteristic of fish fed with soybean-based diets, publishable reported in numeral carnivore fishes including rainbow trout, chinook salmon (Bureau et al, 1998), Asian sea bass (Ma et al, 2018;Tantikitti et al, 2005), spotted rose snapper (Lutjanus guttatus) (Silva-Carrillo et al, 2012), silvery-black porgy (Sparidentex hasta) (Yaghoubi et al, 2016) and red sea bream (Tola et al, 2019a(Tola et al, , 2019b). Decreased feeding rates of Asian sea bass fed with the LFM diet were possibly attributed to antinutritional factors in soybean meal.…”
Section: Growth Performance and Feed Utilizationmentioning
confidence: 99%